Pengaruh Religiusitas, Transparansi, Kepercayaan, Pendidikan dan Minat Sebagai Variabel Mediasi Terhadap Keputusan Muzakki untuk Membayar Zakat pada Baznas Provinsi NTB. - Muhamad Wahyudi Rabbi; Irwan, M; Moh. Huzaini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was conducted to investigate the influence of religiosity, transparency, trust, and education on muzakki's decision to pay zakat at BAZNAS NTB, by considering interest as a mediating variable. The research method used is a quantitative approach, with a research population consisting of muzakki in NTB Province and a sample size of 100 respondents. The data analyzed included primary and secondary data. The results of the analysis showed that religiosity, transparency, and education did not have a significant impact other than supporting muzakki's decision. On the other hand, the trust variable has a positive and significant influence. Interest has been proven to be a mediating variable in the relationship between trust and education with muzakki's decision. However, interest failed to mediate the relationship between religiosity and transparency, which also did not show a significant influence on muzakki's decision to pay zakat. In addition, interest has a direct impact on the decision. The R-squared test shows that in a direct relationship, the independent variables can explain 38.3% of the variation in muzakki's decision, while the rest is influenced by factors outside the model. In the indirect relationship mediated by interest, the R-squared value of 37.4% indicates a similar influence from other factors outside the research model.